(untitled) (Marketing Journal, 2025)
This article explores the development of Islamic financial services in Uzbekistan, examining the essence of the Islamic finance system, its historical evolution, and the application of Islamic financial instruments. The study highlights their advantages and analyzes prospects for further improvement. It also outlines key challenges faced in implementing Islamic finance tools in Uzbekistan and provides the author’s recommendations to address them.